News participation is declining: evidence from 46 countries between 2015 and 2022 - Altay, S; Fletcher, R; Nielsen, RK (SAGE Publications, 2024)
Digital media are often praised for having offered new ways to participate with news. But how has participation with news changed in recent years? A pre-registered analysis of survey data from 2015 to 2022 in 46 countries (N = 577,859) shows that participation with news has declined. This decrease is observed in most countries and for most forms of participation, including liking, sharing, commenting on news on social media and talking about the news offline. The only form of participation that has increased is news sharing via private messaging apps. Overall, participation with news was higher among younger people, the university-educated, those with high interest in news and those with low trust in news. Over time, participation has declined more for those with lower trust in news, those without a bachelor’s degree and for women. Within countries, increases in political polarization were associated with lower participation.